Matrix M Adjuvanted H5N1 Vaccine Elicits Broadly Neutralizing Antibodies and Neuraminidase Inhibiting Antibodies in Humans That Correlate With In Vivo Protection - Zhou, Fan; Hansen, Lena; Pedersen, Gabriel; Grødeland, Gunnveig; Cox, Rebecca (Frontiers in Immunology, 2021)
The highly pathogenic avian influenza H5N1 viruses constantly evolve and give rise to novel variants that have caused widespread zoonotic outbreaks and sporadic human infections. Therefore, vaccines capable of eliciting broadly protective antibody responses are desired and under development. We here investigated the magnitude, kinetics and protective efficacy of the multi-faceted humoral immunity induced by vaccination in healthy adult volunteers with a Matrix M adjuvanted virosomal H5N1 vaccine. Vaccinees were given escalating doses of adjuvanted vaccine (1.5μg, 7.5μg, or 30μg), or a non-adjuvanted vaccine (30μg). An evaluation of sera from vaccinees against pseudotyped viruses covering all (sub)clades isolated from human H5N1 infections demonstrated that the adjuvanted vaccines (7.5μg and 30μg) could elicit rapid and robust increases of broadly cross-neutralizing antibodies against all clades. In addition, the adjuvanted vaccines also induced multifaceted antibody responses including hemagglutinin stalk domain specific, neuraminidase inhibiting, and antibody-dependent cellular cytotoxicity inducing antibodies. The lower adjuvanted dose (1.5µg) showed delayed kinetics, whilst the non-adjuvanted vaccine induced overall lower levels of antibody responses. Importantly, we demonstrate that human sera post vaccination with the adjuvanted (30μg) vaccine provided full protection against a lethal homologous virus challenge in mice. Of note, when combining our data from mice and humans we identified the neutralizing and neuraminidase inhibiting antibody titers as correlates of in vivo protection.